PERKEMBANGAN KONSTELASI POLITIK INTERNASIONAL DAN IMPLIKASINYA TERHADAP POLITIK HUKUM NASIONAL INDONESIA DALAM PEMBERANTASAN TERORISME - Mardenis, Mardenis (Jurnal Dinamika Hukum, 2011)
The problem of terrorism has now become one of the few global issues which are very much talked about and greatly affect international relations. Actually, when the United States (U.S.) makes the issue of terrorism as the main agenda of foreign policy (polugri) country and invite / pressing other countries to support it, almost all world countries basically agree, agree. The problem then arises when the execution was terrorism that will be the common enemy of mankind and must be fought together it is terrorism by political interests, and ideology economi U.S. Key words: Terrorism, global issue, US foreign policy, political, economy and ideology of US.